Fear of Movement and Associated Factors Among Adults With Symptomatic Knee Osteoarthritis - GUNN, ALEXANDER H. (Arthritis Care Res (Hoboken), 2017)
OBJECTIVE: To examine the frequency of and factors associated with fear of movement (FOM) among patients with symptomatic knee osteoarthritis (KOA), using the new Brief Fear of Movement (BFOM) measure. METHODS: Participants (n = 350) enrolled in a clinical trial completed the BFOM scale prior to randomization. The relationships of BFOM with the following characteristics were examined: age, sex, race, education, pain and activities of daily living (ADL) subscales of the Knee Injury and Osteoarthritis Outcome Score (KOOS), knee symptom duration, depressive symptoms (8-item Patient Health Questionnaire [PHQ-8]), history of falls and knee injury, family history of knee problems, self-efficacy for exercise (SEE), and unilateral balance test. A proportional odds logistic regression model examined multivariable associations of participant characteristics with a 3-level BFOM variable (agreement with 0, 1–2, or ≥3 items). RESULTS: The majority of participants (77%) agreed with at least 1 item on the BFOM scale, and 36% endorsed 3+ items, suggesting a high degree of FOM. In the multivariable model, the following remained significant after backward selection: age (odds ratio [OR] 0.79 per 10-point increase, 95% confidence interval [95% CI] 0.66–0.95), KOOS ADL (OR 0.86 per 10-point increase, 95% CI 0.76–0.97), PHQ-8 (OR 1.15, 95% CI 1.08–1.22), and SEE (OR 0.87 per 10-point increase, 95% CI 0.78–0.96). CONCLUSION: FOM was common among patients with symptomatic KOA, and this could negatively impact physical activity. Psychological variables were significantly associated with FOM, suggesting behavioral and psychological interventions may decrease FOM and improve outcomes among individuals with symptomatic KOA.